PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2008-2012) - Minanti Kusumowati; Wahyu Meiranto (Diponegoro Journal of Accounting, 2014)
The purpose of this study is to provide an empirical evidence about the influence of intellectual capital on company performances that is identified using an input-process-output concept of human, customer, innovative and process capitals, on company performances. Based on Resourced-Based Theory and intellectual capital perspective,  the structural path model is applied to financial data to analyze the relationships among the four componentsof intellectual capital, as well as the causal effects of intellectual capital on company performance.Data that used in this study is secondary data, financial reporting 2008 until 2012 which were obtained from the Indonesia Stock Exchange. The population of this study are companies that listed in the Indonesia Stock Exchange in from 2008 until 2012. Sample of this study are seventeen companies. Samples were taken by purposive sampling with a sample selection criteria.Results of this study indicate that not all components of intellectual capital significantly influence the performance of the company. Positive effect on innovation to human capital and customer capital. Capital process negatively affect customer capital. Value-added human resources positive effect on customer capital. Customer capital and value-added human resources has a positive effect on firm performance